Cloud Tracking in Jupiter’s Polar Regions Using JunoCam and JIRAM Data - Montminy, Brigitte N. (Tufts Archival Research Center, 2022)
JunoCam and JIRAM (Jovian Infrared Auroral Mapper) are two key instruments on the Juno spacecraft, which has been orbiting Jupiter since 2016. JunoCam takes visible light images while JIRAM focuses on the near-infrared light. This project utilizes data from both instruments to study Jupiter’s atmosphere in order to track meteorological features and develop a deeper understanding of the planet’s atmospheric patterns. Jupiter’s gaseous atmosphere is filled with jetstreams, polar vortices, and folded-filamentary regions (FFRs), all of which are studied in this project. With JunoCam’s images helping us see the cloud tops and JIRAM helping us study the properties of deeper clouds, this project aims to combine data in order to track clouds’ movements over time. After processing the raw images, we are able to stitch them together to create larger mosaics and compare them in order to see how features change over time. This project focuses on tracking clouds, specifically the North Pole Cyclone (NPC), using the MATLAB software Optical Flow. By evaluating the maximum wind speeds, streamlines, and velocity fields, we can gain a deeper understanding of how the cyclones behave and interact. In order to optimize its usage of this software, a design of experiment was conducted to find reasonable settings for each software variable and to assess the sensitivity of the OpticalFlow software variables to process JIRAM imagery. This allows for future work to achieve the most accurate results possible. Upon conducting this experiment, I chose the best results and constrained the main variables.; Thesis (B.S.)--Tufts University, 2022.; Submitted to the Dept. of Physics and Astronomy.; Advisor: Dr. Anna Sajina.